VD_FINDINFO HC / 2016 / 827 vom 25. August 2016 - VD Tribunal cantonal (2016)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS, SÛRETÉS, DÉLAI, PROLONGATION | 837 al. 1 ch. 3 CC, 839 al. 2 CC, 839 al. 3 CC, 961 al. 3 CC, 308 al. 1 let. b CPC (CH)